The effects of empathetic transformational leadership on group commitment and cooperation : an experimental study - Santos, Pedro Miguel Teixeira Pereira (2022)
The concept of leadership has been constantly adjusted and adapted over time, and there is no clear definition of this concept. In this way, our study aims to understand the impact that certain leadership characteristics, including empathy, have on the dynamics of the followers as a group, whether in their commitment or cooperation with the group. To this end, we developed a questionnaire with the participation of 80 individuals, dividing it into two parts: decision making and self-report. In the decision making part, with the use of the "Public Good Game", it was possible to measure cooperation, while in the self-report it was possible to measure the perception that the participants have of their leader, measuring the various characteristics of the leader. The results allowed us to confirm that leadership, whether transformational or transactional, is highly correlated with empathy; allowed us to confirm that group commitment is positively correlated with cooperation; and allowed us to conclude that, in this particular case, only transactional leadership correlates with group commitment, confirming that in the competitive and dynamic market in which we conducted the study, the fashion retail market, reward works as a determining factor to ensure high levels of group commitment.